A Case Survey on the Living Habits and Awareness of Food Waste Composting in Layang-Layang, Johor (Journal of Tropical Resources and Sustainable Science (JTRSS), 2025)
Food waste management is a critical issue in modern urban landscapes. This study investigated the living habits and awareness of food waste composting in Kampung Jaya SC Sepakat community, Layang-Layang, Johor. An analysis of 273 participants in the survey study revealed that the community had varied living habits and the rates of food waste composting ranged from 40% to 80%. There was a clear correlation between knowledge about composting and the adoption of sustainable behaviors that minimized food waste within this community. A significant number of participants also demonstrated knowledge of household composting equipment and stated a strong inclination to make use of it. The study has generated valuable insights for potential food waste management practices and environmental organizations in the efforts of food waste reduction and composting.
Keywords: groceries; habit; household; organic; sustainability